Local Religious Values of Javanese-Sundanese Religion: Resistance to Modernity - Susanto, Nanang Hasan; Basid, Abdul (LP2M - Universitas Islam Negeri Walisongo Semarang, 2024)
Modernity can erode traditional values, particularly religion. Local religions often reflect community cultural values more prominently, resulting in stronger traditional aspects than mainstream religions. This research investigates the educational principles established by Madrais, the founder of the Javanese-Sundanese Religion (Agama Djawa-Soenda/ADS), aimed at the indigenous population regarding resistance to modernity. Central to ADS is the promotion of harmony with the natural environment. Nevertheless, this principle can also be examined through the lens of resistance to modernity and the potential imposition of external values that may jeopardize the integrity of their traditional beliefs, including foreign religions. Viewed in this context, ADS represents a dual commitment to environmental sustainability and safeguarding traditional cultural values. The analytical framework is grounded in value education theory and the theory of modernity rationalization. Data for this study were collected through a literature review of manuscripts authored by Madrais, alongside interviews with prominent figures within the ADS community. The findings indicate that the teachings of ADS inherently reflect a robust resistance to modernity. This resistance is particularly evident in three key tenets: rejecting all forms of colonialism, encouraging harmony with nature and returning to authentic human identity, and the imperative to honor and protect customs and traditions. These three principles are interconnected and share a common underlying ethos. This study highlights the importance of providing insights into the traditional aspects of local religions as a strong foundation for preserving traditions amidst the onslaught of modernity.